Is using the term wellbeing with students a mistake? Evaluating a wellbeing intervention in a UK Law School - suggestions for repositioning strategies to address the impact of deficit-discourse. Issue 1 (2nd January 2022) - Meyer, Denise; Strevens, Caroline
ABSTRACT: This paper evaluates a curriculum-based and student co-created approach to improving student wellbeing and psychological resilience in a law school. The pilot employed an enhanced pedagogic framework informed by an evidence-based psychological literacy model compatible with self-determination theory (SDT). Level 4 students were introduced to a simple psychological model for recognising the role of emotion regulation in successful learning and the relevance to this of developing supportive connections and a sense of belonging within an inclusive learning community. Student "Wellbeing Champions" received further peer support and leadership training referencing this model and were then supported in developing the role primarily through community-building initiatives. Staff were also issued with a bespoke "Student Success" framework, encouraging them to support student motivation and success by incorporating activities for building relationships, creating a sense of community and belonging with safety to make mistakes, and scaffolding understanding of assessment and feedback. Recognising the limiting positions offered within a medicalised or deficit-focused narrative about wellbeing and mental health, the findings evaluate the effectiveness of the repositioning strategies represented within the pilot interventions, including a focus on learning success and leadership.